An Innovative Technique in Local Antibiotic Delivery Method in Open Infected Wounds of the Musculoskeletal System. (June 2019) - Shekhar, Chander
Bone and soft tissue infections are difficult problems in orthopedic surgery. Infections resulting in chronic osteomyelitis if established are difficult to eradicate. The delivery of local antibiotics for the treatment of open infected wounds of the musculo skeletal system is a more logical approach to treat these infections. Antibiotics given systemically are unable to achieve minimum inhibitory concentration in areas of infected wounds which are ischemic or relatively avascular. And also these antibiotics given over a prolonged period lead to significant toxicity and side effects and emergence of resistant bacteria. The author has been treating difficult cases of infected wounds sustained in road accidents, wounds (diabetic ulcers) in Diabetes Mellitus with necrotizing fasciitis and post operative infections with discharging sinuses with infected implants inside by his own innovative method of antibiotic delivery. The infected open wounds have been treated by application of Vitamin D3 granules impregnated with Tobramycin or Tobramycin and Vancomycin combined. All the patients responded successfully to this novel method of treatment which is extremely simple, effective, low cost, without any complications or side effects and has shown excellent results. Not only the Vitamin D3 granules act as a carrier of the antibiotic locally but also have properties of boosting immunity, and promote tissue healing. It also produces an antibiotic like substance Cathelicidin which kills bacteria and promotes growth of the bone and restores the bone mineral density.